2014
DOI: 10.1007/s00170-014-5725-7
|View full text |Cite
|
Sign up to set email alerts
|

Force-field instability in surface grinding

Abstract: In this paper, a particular kind of non-regenerative instability in surface grinding is studied. Clear evidences have been collected suggesting that vibrations can occur suddenly even during the first grinding pass, just after wheel dressing. These circumstances exclude workpiece and wheel surface regeneration as instability origin, whereas both surfaces have to be considered initially smooth. On these bases, the stability of the dynamic system constituted by an oscillating ideal wheel (namely without waviness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Pearce [19] studied, both theoretically and experimentally, the effect of the wheel dressing parameters (dresser position, wheel speed and workpiece regeneration) on the cutting instability; he showed that these factors play a key role in mitigating the regenerative chatter onset, with special emphasis on the improvements provided by the continuous dressing technique. Leonesio et al [20] have demonstrated that structural mode shapes can induce a force-field cutting instability in grinding processes, thus confirming standard regenerative phenomenon is not the only reason inducing cutting instability. Mannan et al [21] have studied the effect on chatter onset of the torsional compliance introduced by wheel spindle, considering a linearization of the system dynamics and then applying a frequency domain approach.…”
Section: Nomenclature H0mentioning
confidence: 89%
See 1 more Smart Citation
“…Pearce [19] studied, both theoretically and experimentally, the effect of the wheel dressing parameters (dresser position, wheel speed and workpiece regeneration) on the cutting instability; he showed that these factors play a key role in mitigating the regenerative chatter onset, with special emphasis on the improvements provided by the continuous dressing technique. Leonesio et al [20] have demonstrated that structural mode shapes can induce a force-field cutting instability in grinding processes, thus confirming standard regenerative phenomenon is not the only reason inducing cutting instability. Mannan et al [21] have studied the effect on chatter onset of the torsional compliance introduced by wheel spindle, considering a linearization of the system dynamics and then applying a frequency domain approach.…”
Section: Nomenclature H0mentioning
confidence: 89%
“…The block diagram depicted in Figure 4 represents the wheel regenerative chatter dynamics. The model takes into account 2 DoFs: the displacements in normal and tangential directions, according to the approach proposed by Leonesio et al [20]. These displacements are firstly perturbed by the vibrations induced by grinding force on the wheel-workpiece relative dynamics (i.e.…”
Section: G H S G H S E G H S W S E W S W S E E Ementioning
confidence: 99%
“…Based on these definitions, the following force model is considered, which can be generalized for any kind of wheel-workpiece engagement (see [27], [6]):…”
Section: ω +mentioning
confidence: 99%
“…A two DoFs (degrees of freedom) process modelthat considers also the tangential force component and the corresponding displacementhas been proposed in [6] to deal with cutting instability generated by damping forces acting on vibration modes involving both radial and tangent displacements. Then, an additional coefficient is needed: the ratio between normal and tangential force components.…”
Section: Introductionmentioning
confidence: 99%
“…This laid the foundation for establishing an accurate generating grinding surface topography model. Leonesio [9] predicted the time-domain curve of the grinding force by establishing a time-domain cutting thickness model during the grinding process. They also used the modal experiment method to identify the modal mass, modal stiffness, and damping ratio of the grinding wheel spindle system.…”
Section: Introductionmentioning
confidence: 99%